PROTECTING THE ENVIRONMENT FROM AUTOMOBILE EXHAUST GASES - Abdirashidov Aslidin Abdumuhammad o‘g‘li; Rasuli Khaluddin (Bright Mind Publishing, 2025)
The transport-road complex is a source of environmental pollution. Vehicles have the highest indicators among the factors influencing the change of air. 89 percent of the 35 million tons of harmful waste is the waste of automobile transport and road construction enterprises. In order to reduce the harmful effects of the car, it is necessary to find solutions that satisfy the relevant conditions of the flow of matter and energy exchange between the car transport complex and the environment. Transport is one of the main sources of noise in cities and contributes to thermal pollution of the environment.
Keywords: Automobile, level of automobileization, ecology, atmosphere, dust particles, heavy metals, engine exhaust gases, relative cleanliness indicators.